2013
DOI: 10.1002/14651858.cd009494.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Endovenous thermal ablation for healing venous ulcers and preventing recurrence

Abstract: Endovenous thermal ablation for healing venous ulcers and preventing recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 44 publications
1
26
0
1
Order By: Relevance
“…We also compared these recommendations with the findings of the Cochrane research teams. [6][7][8][9][10] Note that while most guidelines recommended a particular therapy, a few did not mention the therapy or indicated that there was insufficient evidence on which to base a recommendation. For example, WHS, SVS-AVF, and SIGN recommended multi-compression bandages, but HAS made no direct recommendation for a type of pressure compression, and AWMA-NCWC indicated that there is minimal evidence to suggest that one type of compression is better than another.…”
mentioning
confidence: 99%
“…We also compared these recommendations with the findings of the Cochrane research teams. [6][7][8][9][10] Note that while most guidelines recommended a particular therapy, a few did not mention the therapy or indicated that there was insufficient evidence on which to base a recommendation. For example, WHS, SVS-AVF, and SIGN recommended multi-compression bandages, but HAS made no direct recommendation for a type of pressure compression, and AWMA-NCWC indicated that there is minimal evidence to suggest that one type of compression is better than another.…”
mentioning
confidence: 99%
“…Venous ulcers significantly impair quality of life, and their treatment places a heavy financial burden upon healthcare systems . Western healthcare systems spend around 1–3% of their budget in this area, and in the U.S.A. alone, treatment of venous ulcers costs around US$3 billion per year …”
Section: What Is Already Known About This Topic?mentioning
confidence: 99%
“…88 Although superficial endovenous thermal ablation is gaining in popularity, there are no randomized, controlled trials about its effects on healing VLUs, quality of life, or its cost effectiveness. 89 The evidence lacks robustness owing to large incompatibilities between the trials and different methods used to measure outcomes; therefore, more research is needed.…”
Section: Surgical Managementmentioning
confidence: 99%